Microbial and Biochemical Analyses of High-Quality, Long-Ripened, Blue-Veined Cabrales Cheese - Javier Rodríguez; Paula Rosa Suárez; Souvik Das; Lucía Vázquez; Sonam Lama; Ana Belén Flórez; Jyoti Prakash Tamang; Baltasar Mayo (Foods)
Sixteen long-ripened, high-quality Cabrales cheeses from independent producers underwent a comprehensive biochemical and microbiological characterisation. Significant variations in total microbial counts and specific microbial groups were observed among the cheeses. A metataxonomic analysis identified 249 prokaryotic amplicon sequence variants (ASVs) and 99 eukaryotic ASVs, respectively, which were classified into 52 prokaryotic and 43 eukaryotic species. The predominant species included bacteria of the genera Tetragenococcus, Lactococcus (of which Lactococcus lactis was used as a starter), and Staphylococcus, followed by Brevibacterium and Corynebacterium species. The starter mould Penicillium roqueforti was highly abundant in all cheeses; Debaryomyces hansenii, Geotrichum candidum, and Kluyveromyces spp. constituted the subdominant fungal populations. Glutamic acid (≈20 mg g−1) was the most abundant free amino acid in all samples, followed by lysine, leucine, and valine (≈10–13 mg g−1). Moderate-to-high amounts of the biogenic amines tyramine and ornithine were detected. A large variation between cheeses of the main organic acids (lactic, acetic, or butyric) was detected. Differences between samples were also observed for the majority volatile compounds, which included organic acids, alcohols, esters, and ketones. Positive and negative correlations between bacterial and fungal species were detected, as well as between microbial populations and key biochemical markers. Among the latter, Tetragenococcus halophilus correlated positively with ethyl caprylate and hexanoic acid, and Loigolactobacillus rennini correlated positively with γ-aminobutyric acid. Conversely, Staphylococcus equorum showed a strong negative correlation with ethyl caprylate and capric acid. These microbial and biochemical insights enabled us to propose a microbiota-based starter culture comprising prokaryotic and eukaryotic components to enhance Cabrales cheese quality.